Critical Thinking in 21st Century Learning: The Impact of Artificial Intelligence (AI) on Teaching English as a Foreign Language (TEFL)-A Philosophical Perspective - Muslim Fikri (English Language Education Department, Universitas Majalengka, 2024)
Abstract: About the use of Artificial Intelligence (AI) in the context of Teaching English as a Foreign Language (TEFL), numerous articles have discussed its impact, ranging from positive to negative effects. Although the majority of literature asserts that AI has a significantly positive impact, this research aims to evaluate and critically analyze these effects. The focus of this study is on the variables of critical thinking, the impact of AI on TEFL, and philosophical perspectives. This research employs a qualitative approach with document analysis methods, beginning with the selection of documents based on authenticity, credibility, representativeness, and meaning factors. The research findings support the positive effects of using AI in TEFL, emphasizing the improvement of students' English language skills in speaking and writing, particularly in terms of grammar. However, the research highlights the importance of specific conditions that must be met for these positive impacts to be achieved. A critical analysis of AI's impact on TEFL reflects the necessity of incorporating critical thinking in this research to avoid uncertainties. The study also explores philosophical views related to ontology, epistemology, and axiology. In the ontological perspective, AI aids students in understanding existence and reality in language learning, especially concerning vocabulary, phrases, and grammar. From an epistemological perspective, AI serves as a foundation for students' knowledge acquisition by presenting tailored learning materials and supporting a deep understanding of linguistics. Meanwhile, from the axiological perspective, the use of AI creates positive values such as accessibility, diversity, and equality in education.